PENERAPAN KETERAMPILAN MENULIS KARANGAN NARASI DENGAN MENGGUNAKAN MODEL PEMBELAJARAN CONCEPT SENTENCE PADA SISWA SEKOLAH DASAR - Aklilah Zulkifli; Yenni Fitra Surya; Fadhilaturrahmi; Sumianto; Yanti Yandri Kusuma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low narrative writing skills of fifth-grade students at UPT SDN 019 Muara Uwai in the Indonesian language subject. The study aims to improve students’ narrative writing skills by using the Concept Sentence learning model. This research employs a Classroom Action Research (CAR) method consisting of two cycles. The research subjects were 15 fifth-grade students at UPT SDN 019 Muara Uwai. Data collection techniques used were observation, tests, and documentation. The research instruments included teacher and student activity observation sheets, as well as narrative writing skill tests. The data analysis technique used was descriptive. The results showed an improvement in students’ narrative writing skills. In the pre-action stage, the students’ average score was 36.33 with a learning mastery of 20%. After the implementation of the first cycle, the average score increased to 64 with a learning mastery of 33.33%. In the second cycle, the average score further increased to 82 with a learning mastery of 80%. This improvement indicates that the Concept Sentence learning model is effective in enhancing students’ narrative writing skills. The conclusion of this study is that the implementation of the Concept Sentence learning model can improve students’ writing skills in the Indonesian language subject for fifth-grade students at UPT SDN 019 Muara Uwai.